2006
DOI: 10.1038/sj.tpj.6500414
|View full text |Cite
|
Sign up to set email alerts
|

Use of pairwise marker combination and recursive partitioning in a pharmacogenetic genome-wide scan

Abstract: The objective of pharmacogenetic research is to identify a genetic marker, or a set of genetic markers, that can predict how a given person will respond to a given medicine. To search for such marker combinations that are predictive of adverse drug events, we have developed and applied two complementary methods to a pharmacogenetic study of the hypersensitivity reaction (HSR) associated with treatment with abacavir, a medicine that is used to treat HIVinfected patients. Our results show that both of these meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The strategy to investigate potentially useful predictive marker combinations has been applied elsewhere (Warren, et al, 2007). The pair-wise marker combination method can yield a collection of marker pairs that featured a spectrum of sensitivities to specific outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy to investigate potentially useful predictive marker combinations has been applied elsewhere (Warren, et al, 2007). The pair-wise marker combination method can yield a collection of marker pairs that featured a spectrum of sensitivities to specific outcome.…”
Section: Discussionmentioning
confidence: 99%
“…(McCarthy et al, 2008;Frayling, 2007;Zanke et al, 2007;Warren et al, 2007;Zeggini et al, 2007;Sladek et al, 2007;North et al, 2004;Libioulle et al, 2007;Wellcome Trust Case-Control Consortium, 2007;Raelson et al, 2007;Coon et al, 2007;Scott et al, 2007;Hunter et al, 2007;Schymick et al, 2007;Li et al, 2008). The time required to genotype and analyze the data derived from pre-existing clinical collections can be as little as several weeks.…”
Section: Genome-wide Association Interpretationsfthe 'Linkage' Of Thementioning
confidence: 99%
“…Predictive marker combinations may be identified as interaction terms in cross-tabulations, analyses of variance or logistic regression analyses, and data mining tools, such as recursive partitioning, are particularly helpful for this. The situations in which such recursive partitioning should be performed in whole genome scans is not yet clear: in the entire data sets or, as some authors have performed, in subsets identified in a monofactorial analysis as possible risk factors [ 30 ].…”
Section: Role Of Pharmacogenomics In Pvmentioning
confidence: 99%